Association between the soluble epoxide hydrolase gene and preeclampsia - Ismail Sari; Hatice Pinarbasi; Ergun Pinarbasi; Caglar Yildiz (Taylor & Francis Group, 2017)
Objective: In this study the association between K55R polymorphism, methylation level of the EPHX2 promoter region, and PE was investigated in 520 individuals including 260 PE patients and 260 healthy pregnant women. Methods: K55R polymorphism and methylation level of the EPHX2 promoter were determined by the real-time PCR using double-dye hydrolysis probes and methylation-sensitive high-resolution melting analysis, respectively. Results: The presence of the K55R polymorphism was significantly higher in cases (28.1%) than controls (17.3%), and was associated with increased risk of PE (OR: 1.86; 95% CI: 1.09-2.63). Methylation levels of the EPHX2 promoter region in cases were significantly lower than controls. A 2.83 times increased PE risk was observed in pregnant women with EPHX2 promoter methylation levels of <25% (OR: 2.83; 95% CI: 1.15-6.91). Conclusion: In conclusion, hypomethylation of the promoter region of EPHX2 and K55R polymorphism were associated with significant increased risk of PE. sEH enzyme may play a role in the pathogenesis of PE by contributing to reduction of the vasodilatator, anti-hypertensive, and anti-inflammatory effects of EETs by rapid degradation of these molecules.